Evaluation of Risk Management Implementation in Educational Institutions - Handriadi Handriadi; Hafidz Nur Ockta Kustiyanto; Som Chai (Yayasan Adra Karima Hubbi, 2025)
Background. The implementation of risk management in educational institutions has become increasingly crucial due to the growing complexities and uncertainties in the education sector. However, many institutions face challenges in effectively adopting risk management practices, leading to potential vulnerabilities that affect their operational and educational outcomes. Purpose. This study aims to evaluate the current state of risk management implementation in educational institutions, focusing on the strategies, processes, and challenges involved. Method. The research adopts a mixed-methods approach, combining qualitative interviews with key stakeholders (administrators, staff, and educators) and quantitative surveys to assess the extent of risk management practices across several educational institutions. Results. The findings reveal that while risk management practices are recognized as essential, their implementation is often inconsistent and lacks a systematic approach. Key challenges identified include insufficient training, lack of resources, and resistance to change. The study concludes that to enhance the effectiveness of risk management in educational institutions, it is crucial to establish clear policies, provide continuous professional development, and foster a culture of proactive risk identification and mitigation. Conclusion. The research provides valuable insights for educational administrators and policymakers to improve risk management frameworks and ensure the sustainability and resilience of educational institutions.